Zakat Management in Efforts to Alleviate Poverty in the Galang Island Community, Batam City - Ellis Siti Khotijah; Iwan Setiadi (East Asian Journal of Multidisciplinary Research, 2023)
This article discusses the role of zakat governance in efforts to alleviate poverty in the community of Galang Island, Batam City. Galang Island is an area that faces significant challenges in overcoming poverty. This research uses a case study method with a qualitative approach. Data was obtained through in-depth interviews with zakat managers, zakat recipients and related parties. The research results show that good zakat governance has a positive impact on poverty alleviation through efficient zakat collection and distribution, transparency in the management of zakat funds, and empowerment of recipients through productive programs. Obstacles include a lack of public awareness and the need for Islamic financial education. This study provides guidance for the government, zakat amil institutions, and the community in developing effective zakat governance strategies.